2013
DOI: 10.1111/j.1741-4520.2012.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ethinyl estradiol prenatally and/or after sexual maturity induces endometriotic and precancerous lesions in uteri and ovaries of mice

Abstract: Unrecognizable exposure to estrogenic substance may cause estrogen-dependent diseases, endometriosis and cancer. Pregnant mice (ICR/Jcl, CLEA) were exposed to 0.01 mg ethinyl estradiol (EE2)/kg per day or vehicle (olive oil) through oral intubation from day 11 to 17 of gestation. They delivered their offspring and raised them. When the experimental female F1 mice were at 8 weeks of age, they were not exposed to EE2 or to the same dose of EE2 or to vehicle twice a week until 20 weeks of age. The control female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Mice also develop adenomyosis after treatment regimens with estrogenic compounds or progesterone (P4). 34,35 Neonatal treatment with tamoxifen, a selective estrogen receptor modulator (SERM), reliably produces adenomyotic lesions in mice, and this model has been used extensively for examining adenomyosis pathogenesis and drug screening. 1,36 Though limited in number, a few studies using genetically engineered mice have also reported adenomyosis development, providing insight into genetic abnormalities that may underlie adenomyosis development, such as increased β-catenin activation.…”
Section: Mouse Models Of Adenomyosismentioning
confidence: 99%
See 1 more Smart Citation
“…Mice also develop adenomyosis after treatment regimens with estrogenic compounds or progesterone (P4). 34,35 Neonatal treatment with tamoxifen, a selective estrogen receptor modulator (SERM), reliably produces adenomyotic lesions in mice, and this model has been used extensively for examining adenomyosis pathogenesis and drug screening. 1,36 Though limited in number, a few studies using genetically engineered mice have also reported adenomyosis development, providing insight into genetic abnormalities that may underlie adenomyosis development, such as increased β-catenin activation.…”
Section: Mouse Models Of Adenomyosismentioning
confidence: 99%
“…Reports have also demonstrated that adenomyosis develops after exposure to estrogenic agents prenatally or in adulthood either alone or in combination with P4. 9,34,35,[54][55][56] Furthermore, chemical pollutants with known estrogenic effects have demonstrated the ability to precipitate adenomyosis development after prenatal, neonatal, or even transgenerational exposure. 57,58 Overall, though it is clear that systemic exposure to various hormonal agents causes or enhances murine adenomyosis development, studies to date have not been detailed or consistent enough to determine the exact mechanism of the affect.…”
Section: Modelmentioning
confidence: 99%
“…This study suggests that continuous EE2 exposure can promote the development of adenomyosis. Using a very different model, Otto et al ., [ 151 ] also demonstrated an important role of estrogen in the development of adenomyosis. This study examined the influence of the estrogen modulating compounds Faslodex and cetrorelix in SHN mice.…”
Section: Drivers Of Co-morbidities Associated With Endometriosismentioning
confidence: 99%
“…SHN mice have been found to develop adenomyosis after pituitary grafting, which leads to an altered endocrine profile. The GnRH antagonist cetrorelix and the estrogen receptor antagonist Faslodex, which negatively interfered with estrogen-mediated signaling, completely inhibited development of adenoymosis, whereas danazol, was slightly less effective in inhibiting disease in SHN mice [ 151 ].…”
Section: Drivers Of Co-morbidities Associated With Endometriosismentioning
confidence: 99%
“…28 Ethinyl estradiol is considered a category X medication in pregnancy because the administration of the drug is related to tumorigenesis and the development of reproductive organs. 27 Furthermore, Koike et al 29 explored the effects of EE2 in animals and found that prenatal exposure may increase the sizes of the endometriotic and precancerous lesions in the uteri and ovaries of mice. In their study, pregnant mice were administered oral EE2 between gestational days 11 and 17, and the offspring were euthanized at 28 weeks of age.…”
Section: Ethinyl Estradiol and Diethylstilbestrolmentioning
confidence: 99%